Melt dripping and flammability behaviour of biodegradable natural fibre - Reinforced thermoplastic composites - (:unkn) unknown (European Conference on Composite Materials, ECCM, 2012)
This work reports the fabrication of jute fibre-reinforced polypropylene (PP) and polylactic acid (PLA) composites using a novel patented nonwoven technology. The water absorption, physical, mechanical and flammability properties of these partially (jute/PP) and fully biodegradable (jute/PLA) composites have been studied and compared with similarly produced glass-fibre reinforced composites with a view to enabling their use in automotive applications. The fibre reinforcements in composites reduced the rate and propensity of burning compared to respective neat resins. There was no melt/flame dripping observed in any of the fibre-reinforced composites.
Keywords: Cone calorimtery; Flammability; Melt dripping; Natural fibre-reinforced composites